The Challanges of Islamic Bank for Accelerating the Growth of Micro, Small and Medium Enterprises (MSMEs) in Indonesia - Suharto, Suharto; Fasa, Muhammad Iqbal (Li Falah: Journal of Islamic Economics and Business, 2017)
Islamic banking has a huge role in accelerating the growth of Micro, Small and Medium Entrerprises(MSME)s in Indonesia. The largest Muslim population in Indonesia is one factor for the developmentof MSMEs. This paper explains how the Problems and Challenges of MSMEs in Indonesia;Development of MSMEs in Indonesia; Relationship Between Islamic Bank and MSMEs in Indonesia;The Role of Islamic Bank for Development MSMEs; and The Challanges of Islamic Bank forAccelerating the Growth of MSMEs in Indonesia. The end of this paper, the authors offer solutions toIslamic banking challenges in accelerating the growth of MSMEs such as: First, to improvemudhorobah and musyarakah financing schemes to accelerate and develop MSMEs in Indonesia;Secondly, to reduce the dependence on the use of Murabahah contract products that are consumptiveand targeted middle and upper only, Third, improve the financing scheme Qordhul Hasan contract bycooperating against Islamic social institutions, such as BAZNAS, BAZDA, LAZ, BWI, and Mosque,etc by maximizing the utilization of zakat funds, infaq, alms, waqf which has been only consumptive.Fourth, the cooperation of linkage program to BPRS and BMT so that the funds channeled can bedirected to remote areas and on target. Fifth, coaching, mentoring, and mentoring to BPRS, BMT,MSMEs business practitioners, and Islamic social institutions in order to develop funds that are storedproductively. Sixth, allocate Hajj and umroh investment funds to MSMEs business practitioners.